Renal and cardiovascular effects of Bothrops marajoensis venom and phospholipase A(2) - Evangelista, Inez Liberato; Costa Martins, Alice Maria; Falcao Nascimento, Nilberto Robson; Havt, Alexandre; Azul Monteiro Evangelista, Janaina Serra; Sa de Noroes, Terentia Batista; Toyama, Marcos Hikari [UNESP]; Diz-Filho, Eduardo Brito [UNESP]; Toyama, Daniela de Oliveira; Fonteles, Manasses Claudino; Azul Monteiro, Helena Serra (Pergamon-Elsevier B.V. Ltd, 2010)
Bothrops marajoensis is found in the savannah of Marajo Island in the State of Par S and regions of Amapa State, Brazil. The aim of the work was to study the renal and cardiovascular effects of the B. marajoensis venom and phospholipase A(2) (PLA(2)). The venom was fractionated by Protein Pack 5PW. N-terminal amino acid sequencing of sPLA(2) showed amino acid identity with other lysine K49sPLA(2)s of snake venom. B. marajoensis venom (30 mu g/mL) decreased the perfusion pressure, renal vascular resistance, urinary flow, glomerular filtration rate and sodium tubular transport. PLA(2) did not change the renal parameters. The perfusion pressure of the mesenteric bed did not change after infusion of venom. In isolated heart, the venom decreased the force of contraction and increased PP but did not change coronary flow. In the arterial pressure, the venom and PLA(2) decreased mean arterial pressure and cardiac frequency. The presence of atrial flutter and late hyperpolarisation reversed, indicating QRS complex arrhythmia and dysfunction in atrial conduction. In conclusion, B. marajoensis venom and PLA(2) induce hypotension and bradycardia while simultaneously blocking electrical conduction in the heart. Moreover, the decrease in glomerular filtration rate, urinary flow and electrolyte transport demonstrates physiological changes to the renal system. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Bothrops marajoensis; Phospholipase A(2); Kidney; Heart; Pressure